Dynamics of changes in local immunity of the oral cavity among the young patients during orthodontic treatment - V. S. Soldatov; M. E. Malyshev; L. N. Soldatova; A. K. Iordanishvili (Медицинская иммунология, 2025)
The development of simple and accessible tools for improvement of dental health over active period of orthodontic treatment with fixed arch appliances (bracket system) is a pressing issue in clinical dentistry. The aim of this study was to investigate the effects of regular usage of oral care products on mucosal immunity in young people undergoing active period of orthodontic treatment using fixed arch appliances. The study involved 39 persons (17 men, 22 women), aged 18 to 28 years, suffering from dentoalveolar anomalies without concomitant somatic pathology. The patients were divided in 2 groups: the comparison group (1) and the main group (2). Patients in Group 1 (16 subjects, 7 men and 9 women), used their usual personal hygiene products throughout the study. Patients in Group 2, (23 persons, 10 men and 13 women) were recommended to use a new domestic low-abrasive toothpaste for sensitive teeth with a triple mechanism of tooth and gum protection, containing copper chlorophyllin at a concentration sufficient to inhibit periodontopathogenic bacteria, calcium glycerophosphate, calcium hydroxyapatite suspension, potassium chloride, silicon dioxide, magnesium chloride and xylitol (R.O.C.S. PRO SENSITIVE). The control age-matched group consisted of 15 people (6 men, 9 women) without dental anomalies and not requiring orthodontic treatment. The biological material was the patients’ oral fluid. The salivary contents of secretory immunoglobulin A, as well as some pro-inflammatory and anti-inflammatory cytokines were determined using the enzyme immunoassay method. The study has revealed unfavorable dynamics in terms of secretory immunoglobulin A, concentrations of pro- and anti-inflammatory cytokines in salivary fluid among young patients using braces at the active stage of orthodontic treatment. The usage of recommended dental and oral care products allowed us to optimize mucosal immunity and normalize the cytokine balance within a month, as well as to maintain it for a long time in complex cases of orthodontic treatment. To maintain dental health during the active period of orthodontic treatment with braces, an algorithm of individual oral care should be kept, by usage of oral hygiene products containing plant-based components with antimicrobial action.